Development of Tourism Potential of Ratu Darah Putih Bathing Site - Haq, M. Irsyad M. Abdul; Muhammad S. Nabilun N; Al Faruq, Dinul Musthafa; Alfian, Dwi Panji; Firdaus, Zahrotul; Sintawati, Sintawati; Astuti, Indah; Wulandari, Septi; Putri, Devi Selomitha; Alif, Fauzi Ahmad Nur; Khasanah, Hijriatun Hikmah; Hidayatullah, Rizky (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2025)
Ratu Darah Putih Bathing Place in Maringgai Village, East Lampung Regency, has significant tourism potential but has not been optimally managed. The main issues include the lack of basic facilities, minimal promotion, low community awareness, unprofessional management, and insufficient attention to the preservation of historical and cultural values. The objectives of this community service program are: (1) to improve the quality of infrastructure and facilities, (2) to enhance promotion and marketing, (3) to increase community awareness and participation, (4) to create professional and sustainable tourism management, and (5) to preserve historical and cultural values. The method used is the Asset Based Community Development (ABCD) approach with five stages: Discovery (identifying local assets), Dream (formulating a shared vision), Design (designing the program), Define (determining priorities), and Destiny (implementing the program). The results of the program show improvements in basic facilities such as the creation of directional signs, tourism banners, and the repair of toilets and parking areas. Promotion efforts through social media and websites have been carried out as an initial step to increase the destination's visibility. The active participation of the community in this program has raised awareness of the importance of maintaining cleanliness and preserving historical and cultural values. The conclusion of this program is that the ABCD approach successfully addressed the challenges and achieved the goal of sustainable tourism development. This program is expected to provide economic and social benefits for the Maringgai Village community.